A Collaborative Strategy for Developing the Competencies of Civil Servants at the Center for Legislative Human Resources Competency Development, Secretariat General of the People’s Representative Council of the Republic of Indonesia - Johansyah Febriyanto; Bambang Giyanto (Journal of Social Research, 2026)
The development of competencies among State Civil Apparatus (ASN) is a critical factor in strengthening bureaucratic performance, particularly within legislative institutions facing rapid organizational and technological changes. This study aims to formulate a collaborative strategy for enhancing ASN competencies at the Center for Legislative Human Resources Competency Development, Secretariat General of the House of Representatives of the Republic of Indonesia. A qualitative descriptive approach was employed, utilizing purposive sampling of ten key informants representing strategic and technical roles. Data were collected through semi-structured interviews and document analysis, and analyzed using the interactive model of Miles and Huberman. The findings reveal that competency development remains fragmented, characterized by weak integration of talent management, persistent silo mentality, regulatory inconsistencies, and suboptimal participation driven by administrative compliance rather than learning motivation. However, cross-unit collaboration initiatives, such as peer-to-peer knowledge sharing and the adoption of digital platforms like Learning Management Systems, demonstrate significant potential to improve accessibility and learning effectiveness. The study concludes that successful competency development requires an integrated collaborative governance framework supported by facilitative leadership, E-HRM integration, and institutionalized coordination mechanisms. These findings contribute both theoretically to collaborative governance literature and practically by offering a strategic blueprint for sustainable public sector human resource development.